Cellular metabolism changes in atherosclerosis and the impact of comorbidities - Dai, Yusang; Junho, Carolina Victoria Cruz; Schieren, Luisa; Wollenhaupt, Julia; Sluimer, Judith C.; van der Vorst, Emiel P. C.; Noels, Heidi (Frontiers in Cell and Developmental Biology, 2024)
Cell activation and nutrient dysregulation are common consequences of atherosclerosis and its preceding risk factors, such as hypertension, dyslipidemia, and diabetes. These diseases may also impact cellular metabolism and consequently cell function, and the other way around, altered cellular metabolism can impact disease development and progression through altered cell function. Understanding the contribution of altered cellular metabolism to atherosclerosis and how cellular metabolism may be altered by co-morbidities and atherosclerosis risk factors could support the development of novel strategies to lower the risk of CVD. Therefore, we briefly review disease pathogenesis and the principles of cell metabolic pathways, before detailing changes in cellular metabolism in the context of atherosclerosis and comorbidities.In the hypoxic, inflammatory and hyperlipidemic milieu of the atherosclerotic plaque riddled with oxidative stress, metabolism shifts to increase anaerobic glycolysis, the pentose-phosphate pathway and amino acid use. We elaborate on metabolic changes for macrophages, neutrophils, vascular endothelial cells, vascular smooth muscle cells and lymphocytes in the context of atherosclerosis and its co-morbidities hypertension, dyslipidemia, and diabetes. Since causal relationships of specific key genes in a metabolic pathway can be cell type-specific and comorbidity-dependent, the impact of cell-specific metabolic changes must be thoroughly explored in vivo, with a focus on also systemic effects. When cell-specific treatments become feasible, this information will be crucial for determining the best metabolic intervention to improve atherosclerosis and its interplay with co-morbidities.